The Relationship Of Husband Support With IVA Tests In Early Detection Of Cancer Of The Word Of Women In Mother In Aek Paing Atas Village Labuhan Batu Regency In 2022 - Riama Theodora Purba; Astaria Br Ginting; Rawiyani; Febrika Tarigan (LLDIKTI Wilayah 1, 2022)
Cervical cancer is a type of malignant tumor that affects the surface layer (epithelium) of the cervix. This cancer can occur because the surface cells have multiplied and changed properties unlike normal cells. This study aims to determine the relationship between husband's support and the IVA test in early detection of cervical cancer in Aek Paing Atas Village, Kel. Aek Paing Kec. North Rantau Kab. Labuhan Batu in 2022. This type of research is analytic observational with a cross sectional approach. The population is mothers as many as 88 people. The sample in this study was 88 people. The sampling technique was total sampling. Data analysis technique using chi square. The results obtained in this study were from 88 respondents. Based on age The results of the chi-square test showed that the age of the EFA mother had a significant relationship with the visual inspection examination (P<0.05). Based on education The results of the chi-square test showed that the education of EFA mothers had a significant relationship with the visual inspection examination (P<0.05). based on occupation The results of the chi-square test showed that the mother's occupation of EFA had a significant relationship with the visual inspection examination (p<0.05). based on knowledge The results of the chi-square test showed that knowledge of EFA mothers had a significant relationship with VIA examination (p<0.05). It is recommended to the puskesmas to improve health promotion to improve health status.